Problematic Internet Use Rate Among High School Students in Tehran, Iran, 2022 - Arman Naeemi; Marjan Mardani Hamooleh; Mahnaz Ghaljeh; Shima Haghani (نشریه پرستاری ایران)
Background & Aims With the spread of web-based applications among students, problematic Internet use (PIU) is increasing. This study aims of investigate the PIU rate among high school students in Tehran, Iran. Materials & Methods In this descriptive cross-sectional study, 256 second-year high school students in Tehran city were included using a convenience sampling method in 2022. The data collection tools were a demographic form and the problematic internet Use questionnaire (PIUQ). The collected data was analyzed in SPSS software, version 16 using descriptive and inferential statistics (independent t-test, analysis of variance). Results The mean total score of PIUQ was 50.27±8.19 out of 100. Among the PIUQ domains, social interactions had the highest mean (2.59±0.55), while adverse effects had the lowest mean (2.44±0.51). There was no significant difference in the PIUQ score based on any demographic variables (P>0.05). Conclusion The development of educational programs by high school officials for students to reduce the adverse effects of PIU is recommended.